Adventures in DeFi-land. (Economist, 2021)
The article focuses on the impact of decentralised finance (DeFi-) on decentralised economy. It mentions that the problems of DeFi-not just the energy intensity of blockchains but the rampant speculation, the potential to be flooded with dirty money and the apparent resistance to regulation-all stand to deter mass adoption. It also mentions that the promise of DeFi is that it could lead to a better kind of finance.